Dansgaard‐Oeschger forcing of sea surface temperature variability in the midlatitude North Atlantic between 500 and 400 ka (MIS 12). (8th November 2014) - Naafs, B. D. A.; Hefter, J.; Stein, R.
Abstract Using a high‐resolution record of alkenone‐based sea surface temperatures (SSTs) from the midlatitude North Atlantic covering the period between 500 and 400 ka here we show that during Marine Isotope Stage (MIS) 12, SSTs in this region were characterized by numerous abrupt jumps in the order of 3–6°C, spaced every 3–4 ka. We argue that these abrupt warming events in the midlatitude North Atlantic reflect Dansgaard‐Oeschger (D/O) events, which are corroborated by the correlation to the synthetic record of Greenland climate for this time period. These results demonstrate that during MIS 12 the direct influence of high‐latitude climate was far larger than during the last glacial and reached all the way into the midlatitude North Atlantic. In addition the consistent temporal lag between surface water cooling and appearance of ice‐rafted debris demonstrates that icebergs were not the cause for cooling in the North Atlantic at this time. We hypothesize that the extreme impact of D/O events during MIS 12 as recorded in our record must have had an imprint on global climate and will therefore be important to evaluate future high‐resolution climate records or model efforts that cover this time period.